Regulation and Internet Use in Developing Countries - Wallsten, Scott (World Bank, Washington, DC, 2014)
Policymakers are simultaneously concerned about the consequences of a worsening "digital divide" between rich and poor countries and hopeful that information and computing technologies could increase economic growth in developing countries. But very little research has explored the reasons for the digital divide beyond noting that it is strongly correlated with standard development indicators, and no empirical research has explored the role of regulation. The author uses data from a unique new survey of telecommunications regulators and other sources to measure the effects of regulation in Internet development. He finds regulation strongly correlated with lower Internet penetration and higher Internet access charges. More specifically, controlling for factors such as income, development of the telecommunications infrastructure, ubiquity of personal computers, and time trends, countries that require formal regulatory approval for Internet service providers (ISPs) to begin operations have fewer Internet users and Internet hosts than countries that do not require such approval. Moreover, countries that regulate ISP final-user prices have higher Internet access prices than countries that do not have such regulations. These results suggest that developing countries' own regulatory policies can have large impacts on the digital divide.